2007
DOI: 10.1007/s00417-006-0441-0
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous methylprednisolone in recent traumatic optic neuropathy; a randomized double-masked placebo-controlled clinical trial

Abstract: Our study confirms earlier findings that there is no difference in visual acuity improvement between intravenous high-dose corticosteroids and placebo in treatment of recent TNO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 16 publications
1
43
1
2
Order By: Relevance
“…The results of these medical and surgical interventions have shown to be uncertain [5][6][7] with possible serious side-effects or complications [8,9]. At present, no study could validate a particular approach to the management of TON [4].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these medical and surgical interventions have shown to be uncertain [5][6][7] with possible serious side-effects or complications [8,9]. At present, no study could validate a particular approach to the management of TON [4].…”
Section: Introductionmentioning
confidence: 99%
“…An important question that needs to be considered when interpreting the current results is whether the improvements in visual acuity seen were the result of levodopa or steroids. Based on the studies that found no benefit of steroid therapy in patients with TON, the visual improvements seen here may be attributable to levodopa (Entezari et al, 2007;Levin et al, 1999). Additionally, the possibility of spontaneous visual acuity improvement cannot be ruled out.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, in a double-blind placebo-controlled clinical trial of 31 patients, Entezari and associates (Entezari et al, 2007) found no benefit resulting from high-dose steroid therapy compared to intravenous normal saline. This was compatible with the International Optic Nerve Trauma Study, a comparative, nonrandomized interventional study that showed that no clear benefit was obtained by either corticosteroid therapy or optic canal decompression surgery (Levin et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The most extensive studies in this regard in the literature have shown that treatment by corticosteroids, surgical decompression, or a combination of both may not be beneficial. 5,6 Spontaneous recovery may occur in 30% of patients. 7 Induced hypothermia, both systemic and local, was studied as a neuroprotective intervention for mitigating secondary neuronal injury that follows the initial damage to the central nervous system after traumatic brain 8,9 and spinal cord 10 injury.…”
mentioning
confidence: 99%